Effects of sorbitol and sodium tripolyphosphate on the quality of fish patty - Jaranilla, Femie Jungco (2008.)
The effect of 4% sorbitol and different levels of sodium tripolyphosphate (STPP) were determined.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Sorbitol; Sodium tripolyphosphate